Simplifying the Technique of Awake Brain Surgery in a Condition of Less Equipped Neurosurgical Institution in Uzbekistan - Mamadaliev, Dilshod Mukhammadvalievich; Kariev, Gayrat Maratovich; Asadullaev, Ulugbek Maksudovich; Yakubov, Jakhongir Bakhodirovich; Zokirov, Kamoliddin Sodikjonovich; Khasanov, Khabibullo Abdukholikovich; Akhmediev, Tokhir Makhmudovich; Korotkov, Dmitriy Sergeyevich (Asian Journal of Neurosurgery, 2023)
Currently, awake craniotomy (AC) is one of the most often employed procedures to map and resect tumors in eloquent brain areas, avoiding the use of general anesthesia (GA) and thereby reducing anesthesia-related complications and cost of surgery. Resource limitations are one of the basic reasons for avoiding AC in low- and middle-income countries (LMICs). The aim of this study is to describe the simplified protocol of awake brain surgery that can be implemented in a limited financial setting in LMICs and to share our first experience. Twenty-five patients diagnosed with tumor of the left frontotemporal lobes, all involving Broca's and Wernicke's areas, were operated on using AC. Brain mapping was executed using mono- and bipolar direct electrical stimulation including cortical and subcortical (axonal) mapping profiles, investigating basically cortical language centers. Neither neuronavigation nor intraoperative magnetic resonance imaging (MRI) was utilized due to financial constraints. AC was performed successfully in 23 of 25 patients, achieving a near-total resection in 16 (69.5%) patients, subtotal resection in 4 patients (17.39%) patients, and partial resection in 3 (13.04%) patients. In two patients, due to psychological instability—agitation and fear during the awake phase—speech test was not technically possible, so they were reintubated by giving them GA. There was no mortality in the early or postoperative period. In spite of the absence of advanced pre- and intraoperative technologies such as intraoperative MRI and navigation systems, AC can be safely performed in LMICs. These tools along with intraoperative cortical mapping and language testing can guarantee better surgical outcomes and quality of life. However, our study confirms that omitting these tools does not make a huge difference in getting good results with AC and that AC is not absolutely impossible. AC can be performed successfully, preserving eloquent brain areas, with minimum and basic set of the armamentarium like system for cortical and subcortical intraoperative neurostimulation which provides cortical/subcortical brain mapping.
Keywords: awake craniotomy; cortical mapping; electrophysiological monitoring; language testing; brain tumor